An Analysis of the Translation of Phrasal Verbs from English to Turkish Existing in “The Lottery” by Shirley Jackson - Baytar, İlknur (Edebi Elestiri Dergisi, 2025)
It is widely known that phrasal verbs are used frequently in English. As phrasal verbs often have a meaning beyond the literal meaning of the components that make up them, transferring these expressions poses some challenges for the translators. Because it requires the translator to be proficient in the source and target languages. However, the translation of phrasal verbs is unavoidable and correct translation of phrasal verbs is important to convey the meaning to the target reader. Considering the explanations, the objective of the article is to illuminate how phrasal verbs are transferred from English to Turkish and to figure out the techniques used by translator. To serve this purpose, Shirley Jackson's “The Lottery” and its Turkish translation titled “Piyango” translated by Armağan İlkin were chosen. And the phrasal verbs in the source text were identified and the techniques used by the translator while translating these phrasal verbs to Turkish, were decided in the framework of the methods put forward by Newmark (1981: 39) that are communicative and semantic translation. To talk about the outcomes; it was found out that the translator used both semantic and communicative translation, but preferred the semantic translation method the most.